Environmental Factors and the Pulmonary Tuberculosis Cases in Bandung City in 2015-2019: an Ecological Study - Atillah, Cecilia Nadine; Wulandari, Ririn Arminsih; Kurniasari, Fitri (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2023)
Introduction: Pulmonary tuberculosis continues to be primary threat to public health by about 10.6 million cases in 2021. Among the countries, Indonesia being the second-largest contributor of tuberculosis cases. Bandung is the city in Indonesia which the incidence of pulmonary tuberculosis has been risen steadily since 2015. However, there is no information about the causes of the risen cases in Bandung city. Methods: Using an ecological study methodology, this study investigated the relationship between the number of pulmonary tuberculosis cases and the environmental factors including of healthy house coverage, population density, and the coverage of families with clean and healthy living behaviors. The correlation test between variables was done with either the Spearman correlation test or the Pearson correlation test, based on the results of the normality test on each data. Results: This study demonstrates a correlation between the coverage of healthy house and population density with the number of pulmonary tuberculosis cases, with both having a p-value of <0.001, but not the coverage of families with clean and healthy living behaviors. Conclusion: It is advisable to empower local communities, utilize the technology as an empowerment facility, and utilize the role of public figures in health promotion to maximize the government efforts to prevent the pulmonary tuberculosis.Keywords: Healthy house, PHBS, Population density, Pulmonary tuberculosis Latar Belakang: Tuberkulosis paru masih menjadi ancaman utama bagi kesehatan masyarakat dengan jumlah kasus sebesar 10,6 di tahun 2021. Di dunia, Indonesia merupakan kontributor kasus tuberkulosis terbesar kedua. Kota Bandung merupakan kota di Indonesia yang insiden tuberkulosis parunya terus meningkat sejak tahun 2015. Namun, tidak terdapat informasi mengenai penyebab kenaikan kasus di Kota Bandung. Metode: Menggunakan metode studi ekologi, studi ini meneliti hubungan antara kasus tuberkulosis paru dengan faktor lingkungan, termasuk cakupan rumah sehat, kepadatan penduduk, dan cakupan rumah tangga berperilaku hidup bersih dan sehat. Uji korelasi antar variabel akan dilakukan menggunakan uji korelasi Spearman atau uji korelasi Pearson, bergantung pada hasil uji normalitasnya masing-masing.Hasil: Studi ini menunjukkan korelasi antara cakupan rumah sehat dan kepadatan penduduk dengan kasus tuberkulosis, dengan keduanya memiliki nilai p sebesar <0,001, namun tidak dengan cakupan rumah tangga berperilaku hidup bersih dan sehat. Kesimpulan. Dari hasil studi ini, disarankan untuk memerdayakan komunitas lokal, memanfaatkan teknologi sebagai fasilitas pemberdayaan, dan memaksimalkan peran figur publik dalam upaya promosi kesehatan untuk memaksimalkan upaya pemerintah dalam usaha pencegahan tuberkulosis paru.Kata kunci: Kepadatan penduduk, PHBS, Rumah sehat, Tuberkulosis paru, Usia